Decyl acetate synthesis by enzyme catalysis in sc-CO2 - Rebocho, Sílvia F. (2010)
The synthesis of decyl acetate, from the transesterification of vinyl acetate with decanol, was studied in a high-pressure experimental set-up, equipped with a variable volume batch reactor, operating isothermally at 35 ºC and 100 bar, using CO2 in supercritical conditions as solvent, and Candida antarctica lipase B (CALB), immobilized on the macroporous resin Lewatit B (Novozym 435®), as catalyst. The enzymatic content was determined for each particle size of the catalyst. It was shown that the smallest particles have a larger specific amount of enzyme, and the results indicate that the enzyme is located in an external shell of the particle, following an “egg-shell” model type, with a thickness of ca. 60 μm (assuming a homogeneous distribution), independent of the particle size. Both external and internal mass transfer resistances were evaluated. External resistances were easily eliminated by stirring and internal diffusional limitations can be considered as negligible. The effect of the feed concentration of substrates on the initial reaction rate was also studied. It was observed that, above a certain concentration of decanol in excess relatively to vinyl acetate, the reaction is inhibited by the alcohol. On the contrary, the reaction is favoured when the reactor is fed with excess of vinyl acetate, with a significant enhancement of its initial rate. These results are consistent with a Ping-pong bi-bi type mechanism with competitive inhibition by the alcohol, commonly used in the description of enzymatic reactions of esterification/ transesterification.